Genomic and phenotypic characterization of a red-pigmented strain of Massilia frigida isolated from an Antarctic microbial mat - Shaffer, Jacob M. C.; Giddings, Lesley-Ann; Samples, Robert M.; Mikucki, Jill A. (Frontiers in Microbiology, 2023)
The McMurdo Dry Valleys of Antarctica experience a range of selective pressures, including extreme seasonal variation in temperature, water and nutrient availability, and UV radiation. Microbial mats in this ecosystem harbor dense concentrations of biomass in an otherwise desolate environment. Microbial inhabitants must mitigate these selective pressures via specialized enzymes, changes to the cellular envelope, and the production of secondary metabolites, such as pigments and osmoprotectants. Here, we describe the isolation and characterization of a Gram-negative, rod-shaped, motile, red-pigmented bacterium, strain DJPM01, from a microbial mat within the Don Juan Pond basin of Wright Valley. Analysis of strain DJMP01’s genome indicates it can be classified as a member of the Massilia frigida species. The genome contains several genes associated with cold and salt tolerance, including multiple RNA helicases, protein chaperones, and cation/proton antiporters. In addition, we identified 17 putative secondary metabolite gene clusters, including a number of nonribosomal peptides and ribosomally synthesized and post-translationally modified peptides (RiPPs), among others, and the biosynthesis pathway for the antimicrobial pigment prodigiosin. When cultivated on complex agar, multiple prodiginines, including the antibiotic prodigiosin, 2-methyl-3-propyl-prodiginine, 2-methyl-3-butyl-prodiginine, 2-methyl-3-heptyl-prodiginine, and cycloprodigiosin, were detected by LC-MS. Genome analyses of sequenced members of the Massilia genus indicates prodigiosin production is unique to Antarctic strains. UV-A radiation, an ecological stressor in the Antarctic, was found to significantly decrease the abundance of prodiginines produced by strain DJPM01. Genomic and phenotypic evidence indicates strain DJPM01 can respond to the ecological conditions of the DJP microbial mat, with prodiginines produced under a range of conditions, including extreme UV radiation.